PENGARUH LEVEL PEMBERIAN PUPUK ECO FARMING (EF) TERHADAP PERTUMBUHAN DAN PRODUKSI RUMPUT GAJAH (Pennisetum purpureum Cv. Pakchong): Effect of Eco-Farming (EF) Fertilizer Levels on Growth and Production of Elephant Grass (Pennisetum purpureum Cv. Pakchong) - Budiman, Budiman; Nurjaya, Nurjaya (Buletin Nutrisi dan Makanan Ternak, 2022)
This study aimed to determine the effect of the level of application of ecofarming fertilizer on the growth, production, and production of forage elephant grass Cv. Pakchong. The experiment was arranged in a completely randomized design with four treatments and four replications. The treatments consisted of: P0 = 0 ml EF + 100 ml water (control); P1 = 4 ml EF/polybag + 100 ml water; P2 = 6 ml EF/polybag + 100 ml water; P3 = 8 ml EF/polybag + 100 ml water. The results showed that using different eco-farming fertilizers had no effect (P>0.05) on plant height, number of tillers, number of leaves per plant, leaf length and width, stem dry matter production, forage dry matter production, leaf stem ratio, but did have an effect (P<0.05) on leaf dry matter production. It was concluded that the application of eco-farming fertilizer level did not affect the growth parameters and dry matter production of stems but did affect the increase in leaf dry weight of elephant grass Cv. Pakchong.